THE PROPOSED LEGALIZATION OF PROSTITUTION IN SOUTH AFRICA – FRAMING THE DEBATE FROM A LIBERAL PERSPECTIVE - Stephen Peté (Obiter, 2021)
The debates surrounding the issue of whether or not prostitution or sex work ought to be legal or illegal have a long and convoluted history, both in South Africa and abroad. This article seeks to provide greater clarity and focus to current debates on this complex issue, in particular from a liberal perspective. By examining certain of the main issues at stake for those committed to the broad tenets of liberal ideology, the article hopes to bring at least some measure of clarity and focus to a contentious set of theoretical and empirical questions. It is argued that, from a liberal perspective, to interfere with the freedom of each South African to make his or her own moral choices is to interfere with the very foundation of South Africa’s hard-won constitutional democracy. In order to convince those committed to truly liberal principles of the need for the criminal law to prohibit sex work, it must be shown that it causes either “harm” or “offence” to others. Liberals will accept neither the principle of “legal moralism” nor that of “legal paternalism” as legitimate reasons to criminalize sex work.